Handwriting examinations in Poland - Leśniak, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The present text is about situation of handwriting examinations currently in Poland. The scientific condition of handwriting examinations and the position taken in practice were presented. In context of statistical date this kind of expert’s opinion may be very significant for judicial proceedings. Meanwhile, the court decision-makers are not appropriately trained for making an assessment of experts’ opinions. Qualifications of handwriting experts are often poor. The dispute about scientific character of comparative examinations is continued. The system of controlling of expert’s opinions quality is not introduced. At the same time Polish scientists do a lot of interesting research on different issues concerning handwriting. Inter alia the researchers deal with: measuring of handwriting characteristics, influences somatic or mental disorders on handwriting, new techniques of graphical and comparative analysis, frequency signatures’ characteristics.
Keywords: badanie pisma ręcznego; opinia biegłego; charakterystyka pisma; badanie porównawcze; badania kryminalistyczne w Polsce; konluzja biegłego; jakość badania kryminalistycznego; kryteria metody naukowej